Cechy wizerunku politycznego a emocje w głosowaniu na Bronisława Komorowskiego i Jarosława Kaczyńskiego w wyborach prezydenckich w 2010 roku. Raport z badań postaw politycznych studentów - Pawełczyk, Piotr; Jankowiak, Barbara (Przegląd Politologiczny, 2018)
In the theory of political marketing the concept of the image appears crucial when explaining electoral preferences and behaviors. This paper presents a survey into the relations between image factors and liking for the main two candidates in the presidential elections in Poland in 2010. It is widely supposed that the assessment of a candidate’s image should translate into a definite (positive or negative) emotion towards him or her. An empirical analysis of the influence of political images on political attitudes, however, leads to a slightly more modest conclusion regarding the power of such influence. Surveys do not unconditionally confirm the assumption that voter’s emotions are unequivocally determined by a candidate’s image, especially as the decisive factors in stimulating support for a given politician (or party) may be provided by negative emotions evoked by his or her rival. The results of the survey do confirm an observation that has already been noted in the literature, that cognitive judgments of a candidate’s image have a considerably weaker influence on voter preferences than the emotions he evokes.